Analisis Terhadap Etika Profesi Hukum Notaris Dalam Menjalankan Tugasnya Sebagai Pejabat Umum Dalam Pembuatan Akta Autentik - Rizky, Fajar Khaify; Safnul, Doddy; Leviza, Jelly (Talenta Publisher, Universitas Sumatera Utara, 2024)
Notary is a public official who is trusted by the public in the authority to make authentic deeds. In exercising his authority as a legal profession, a notary must uphold legal ethics and the dignity and nobility of his position, because if this is ignored by the notary, it can cause harm to the parties and the notary himself. The problem of this research is how the authority of the notary profession as a public official in making authentic deeds, how sanctions are imposed on violations of the code of ethics of the notary profession. The purpose of this study is to determine and examine the authority of the notary profession as a public official in making authentic deeds and sanctions imposed on violations of the notary profession's code of ethics. Type of normative legal research. Secondary data research data obtained from legal materials. Data collection techniques library research techniques. Qualitative data analysis. Notary is a public official who is authorised to make authentic deeds and has other authorities as in Article 1 number 1 jo. Article 15 of UUJN. Sanctions imposed on violations of the code of ethics of the notary profession as in Article 6 paragraph (1) of the Code of Ethics of Notaries of the Indonesian Notary Association (INI) in the form of reprimand, warning, temporary dismissal from Association membership, honourable dismissal from Association membership, dishonourable dismissal from Association membership.